The English Teacher Language Competency Enhancement: A Discussion of Models and Strategies - Susidamaiyanti; Rita Mahriza; Cut Intan Meutiar (Talenta Publisher, 2023)
The purpose of this paper is to describe the numerous methods and techniques employed to improve the language proficiency of English teachers. English teachers must be able to comprehend and communicate effectively in the language because it is utilized in a variety of situations. The topic of discussion will be the many methods employed to improve the language proficiency of English teachers, and their efficacy in doing so will be assessed. The paper will also look at English teachers' difficulties while attempting to become more fluent in another language. In the end, this essay will present a thorough analysis of the models and techniques employed to help English teachers develop their language proficiency and suggestions for enhancing their language abilities.